RETRACTED: Comparison of Chondroitin Sulfate-E Expression in Benign and Malignant Epithelial Type Ovarian Tumors - Kemala Isnainiasih Mantilidewi (Dep/SMF Obstetri & Ginekologi Fakultas Kedokteran Universitas Padjadjaran, 2025)
Objective: Ovarian cancer is the fifth leading cause of cancer-related death in women, due to late diagnosis and limited screening methods. Chondroitin Sulfate-E (CS-E) has shown potential as biomarkers. This study aims to evaluate CS-E expression in epithelial-type benign and malignant ovarian tumors and its potential as a biomarker using QuPath software.Methods: This observational analytic study used a cross-sectional design. Samples were selected based on histopathology of patients with epithelial-type benign and malignant ovarian tumors from surgeries in 2023. Immunohistochemistry using the GD3G7 antibody was performed to detect CS-E expression in tumor tissues preserved in paraffin blocks at Dr. Hasan Sadikin General Hospital Bandung. Expression was quantified using QuPath software. Statistical analysis used the Mann-Whitney and t-test. Result: No significant difference in CS-E expression was found between malignant and benign tumors (p = 0.492). Demographic factors (age, BMI, menopausal status, and parity) showed no significant differences between groups. Conclusion: CS-E expression has not yet demonstrated potential as a biomarker to distinguish between benign and malignant ovarian tumors.Perbandingan Ekspresi Chondroitin Sulfate-E pada Tumor Ovarium Jinak dan Ganas Tipe Epitel Abstrak Tujuan: Kanker ovarium merupakan penyebab kematian kelima terbanyak terkait kanker pada wanita yang disebabkan oleh keterlambatan diagnosis dan keterbatasan metode skrining. Chondroitin Sulfate-E (CS-E) menunjukkan potensi sebagai biomarker. Penelitian ini bertujuan mengevaluasi ekspresi CS-E pada tumor ovarium jinak dan ganas tipe epitelial serta menilai potensinya sebagai biomarker menggunakan perangkat lunak QuPath. Metode: Penelitian analitik observasional ini menggunakan desain potong lintang. Sampel dipilih berdasarkan hasil histopatologi pasien dengan tumor ovarium jinak dan ganas tipe epitelial dari operasi tahun 2023. Pemeriksaan imunohistokimia dengan antibodi GD3G7 dilakukan untuk mendeteksi ekspresi CS-E pada jaringan tumor yang diawetkan dalam blok parafin di RSUP Dr. Hasan Sadikin Bandung. Ekspresi dianalisis secara kuantitatif menggunakan perangkat lunak QuPath. Uji statistik yang digunakan adalah Mann-Whitney dan uji t. Hasil: Tidak ditemukan perbedaan bermakna dalam ekspresi CS-E antara tumor ganas dan jinak (p = 0,492). Faktor demografis (usia, indeks massa tubuh, status menopause, dan paritas) juga tidak menunjukkan perbedaan bermakna antar kelompok.Kesimpulan: Ekspresi CS-E belum menunjukkan potensi sebagai biomarker untuk membedakan antara tumor ovarium jinak dan ganas. Kata kunci: Biomarker, GD3G7, Glikosaminoglikan, Kanker Ovarium, Kondroitin sulfat RETRACTION NOTICE: This article has been formally retracted. To view the detailed Retraction Statement and reason for withdrawal, please follow this link: https://www.obgynia.com/obgyn/index.php/obgynia/article/view/1144